Rock Mass Preconditioning Methods in Underground Mines and Ways of its Evaluation - state-of-the-art - Fuławka, Krzysztof; Szumny, Marcin; Mertuszka, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Currently, the most serious problem associated with underground mining of deposits is geomechanical hazard, which significantly disrupts the production process and exposes the mining crew to a threat to life and health. As recent achievements in the field of minimizing geomechanical hazards show, rock mass preconditioning is the most effective way to prevent the risk of rock bursts and mining-induced seismic activity in underground mines. In principle, rock mass preconditioning involves reducing rock mass strength parameters by the controlled creation in the fractured zones by introducing an external force inside the rock mass. Most often, this can be achieved using hydrofracturing or blasting.
Keywords: rock mass preconditioning; hydrofracturing; destress blasting; underground mine; geomechanical hazards